Attributes and ecological potentials of dumpsite flora in the peri-urban area of Ibadan, Nigeria (2023)
Dumpsites are spaces used disposal of urban and peri-urban wastes. Their public health concern has not made them to be adequately explored for positive potentials in Nigeria. This study investigated the the floristic structure and comparative potential of a dumpsite with arable farms for conservation and phytoremediation. The study was conducted at a 10-hectare peri-urban Lapite dumpsite (N 07o34.121ʹ, E 003o54.857ʹ) in Ibadan, Oyo State, Nigeria; and three arable farmlands (Control) located 200 m-300 m away from Dumpsite. Stratified sampling was conducted using 414 quadrats (each 1m2) in five strata of dumpsite, and a systematic sampling of flora of farms with 263 quaddrats in 21 transects laid 5 m apart. Data were collected on species composition, abundance,density and frequency of occurence. They were subjected to analysis of Relative importance value (RIV), density, and multivariate analysis. Species with phytoremediation potentials were identified. Ninety one species of herbaceous flora in 33 families and 99 species in 38 families were enumerated on the dumpsite and farmlands respectively. Solanum nigrum L., Tridax procumbens Linn., Amaranthus spinosus Linn., Laportea aestuans (Linn.) chew., Acalypha fimbriata Schum. & Thonn., and Lufa cylindrica Mill were the most dominant species on the dumpsite with RIVs of 8.40, 8.17, 7.54, 7.21, 6.38 and 5.79 respectively. Talinum fruticosum (L.) Juss., Tridax procumbens L., Euphorbia heterophylla Linn., Spermacoce ocymoides Burm f., and Tithonia diversifolia (Hemsl.) A. Gray were most dominant on farmlands with RIVs of 13.74, 7.05, 6.60, 6.07, and 5.57 respectively. Dumpsite flora had higher diversity (H`=3.501) than control plots (H`=3.294). The dominance value (0.0486) was low compared to the control farms (0.07131). The lora of the two sites were grouped by habitatt preference.Higher species diversity and pervasive presence of invasive Tridax procumbens linn., Laportea aestuans (Linn.) chew., and Lufa cylindrica Mill. On dumpsite indicated potentials for phytoremediation, and candidacy as functional groups and bio-indicators of ecosystem health.